Pelatihan Pembuatan Detergen Cair, Pelembut dan Pewangi Pakaian Serta Pemasarannya di Nagari Talang - Suciati, Dwimaryam; Pelita, Elda; Elfina, Sri; Subriadi, Fejri; Hafnimardiyanti, Hafnimardiyanti (Journal of Industrial Community Empowerment, 2022)
Talang is a village in Gunung Talang District, Solok Regency, West Sumatera. Nagari Talang, which is located ± 15 km from the city of Solok and ± 50 km from the city of Padang, is the administrative center of Gunung Talang District. The livelihood of the population, in general, is farming, and a small part as traders (entrepreneurs) and government employees. With limited employment opportunities, it is very necessary to provide counseling and training to create jobs and advance industry in the trade sector in the Talang area by utilizing housewives to be able to have their income by producing superior products, namely liquid detergent, fabric softener, and deodorizer. These three products are the main products used in washing and ironing clothes. It is hoped that by producing these products, the community can be helped in terms of the economy, and in particular it can be used as a source of income for housewive organizations in opening laundry. In addition to making these products, the community service team also provides ideas and product marketing systems that can be developed in the Talang community.